Interfacial regulation of aqueous synthesized metal-semiconductor hetero-nanocrystals - Li, Shouyuan; Sun, Shaoyang; Li, Xinyuan; Zhang, Jiatao (Frontiers in Materials, 2022)
Integrating metal and semiconductor components to form metal-semiconductor heterostructures is an attractive strategy to develop nanomaterials for optoelectronic applications, and the rational regulation of their hetero-interfaces could effectively influence their charge transfer properties and further determine their performance. Considering the natural large lattice mismatch between metal and semiconductor components, defects and low crystalline heterointerfaces could be easily generated especially for heterostructures with large contacting areas such as core-shell and over quantum-sized nanostructures. The defective interfaces of heterostructures could lead to the undesirable recombination of photo-induced electrons and holes, which would decrease their performances. Based on these issues, the perspective focusing on the most recent progress in the aqueous synthesis of metal-semiconductor heterostructures with emphasis on heterointerface regulation is proposed, especially in the aspect of non-epitaxial growth strategies initiated by cation exchange reaction (CER). The enhanced optoelectronic performance enabled by precise interfacial regulations is also illustrated. We hope this perspective could provide meaningful insights for researchers on nano synthesis and optoelectronic applications.